Seeing Queerness in Ibsen’s Pillars of Society - Ellen Rees (Edda)
This article presents a queer reading of Henrik Ibsen’s Pillars of Society (1877). This reading of the “gender trouble” in the play arises out of what might be called its “genre trouble”; the author claims that Ibsen makes use of the ambiguities of the lystspill genre in order to satirize idealist discourses regarding patriarchy and capitalism. Building on reflections on queerness in Judith Jack Halberstam’s The Queer Art of Failure (2011) and Sara Ahmed’s The Promise of Happiness (2010), the article then explores forms of resistance to heteronormativity visible in the characters Lona Hessel, Marta Bernick, and Hilmar Tønnesen.